Un cadre descriptif pour la syntaxe du verbe breton - Steve Hewitt (La Bretagne Linguistique, 1988)
The aim of this article is not so much to describe the syntactic facts of the Breton verb, which are more or less well known, as to provide a framework which will help us to understand how and why, and which will explain to some extent the correspondence that can be observed between certain patterns. If the proposed framework cannot provide all the right answers, we hope that it will at least help to ask the right questions in order to explore the issue further.